Several physical properties of Eucalyptus pellita F. Muell from different provenances and sampling position on tree - Karnita Yuniarti; Arif Nirsatmanto (Foresty Faculty of Hasanuddin University, 2018)
Eucalyptus pellita F. Muell is one of the species selected for the development of the plantation forest in Indonesia. In order to obtain a superior plant for the continuity of the plantation forest program, various tree breeding techniques are often applied, one of which is through best provenance selection. Conventional or advanced tree breeding program generally aims to obtain a fast-growing plant with good physical appearance. The program rarely gives attention to the properties/characteristics of timber produced. This aspect becomes the main background of this particular study which aims to investigate the effect of four provenances and also to examine the effect of sampling position on the trees on several physical properties of E. pellita. The result showed that the highest moisture content (97.34 + 15.67%) was found in the bottom part of trees from Indonesia provenance. While, the highest air-dry moisture content (15.15 + 0.20%) was observed in the top-part samples from Provenance North Kiriwo PNG. Samples from Provenance Serisa Village PNG have the highest density ranges, approximately 590 + 90 kg/m3 and 630 + 80 kg/m3 in the bottom-part samples and in the top-part samples, respectively. The highest T/R ratio, approximately 1.91 + 0.26, was observed in the bottom[1]part samples from Provenance South Kiriwa, PNG. The T/R ratio values of all provenances were less than 2, indicating the lumber will be possibly stable during its uses or further processing. Further result showed provenance factor significantly affect initial moisture content and density. Sampling position on trees only affect affects the initial moisture content. Based on the results, the timber of E. pellita being examined can be further used for light-to-medium construction purpose.